Numerical analysis and structural improvement of a sedan after highway chain collisions using the finite element method - Nguyễn, Văn Việt; Cao, Văn Dũng; Đỗ, Hùng Chiến (Journal of Transportation Science and Technology, 2026)
Multiple-vehicle collisions on highways constitute one of the most severe types of traffic accidents in Vietnam, particularly those involving sedan vehicles sandwiched between large trucks. This study employs the finite element method (FEM) using LS-DYNA software to analyze the structural deformation of a sedan vehicle (Dodge Neon model) in multiple collision scenarios across a speed range of 20-60 km/h. The results reveal that intrusion into the passenger compartment exceeds the "Poor" threshold as per Insurance Institute for Highway Safety (IIHS) standards at speeds above 50 km/h, with primary concentrations at the A-pillar, longitudinal beam, and firewall. The proposed enhancement, incorporating an energy-absorbing beam (hemispherical trigger, DP600 steel), reduces intrusion by 40-54% and increases specific energy absorption (SEA) by 18%. This research provides a scientific basis for enhancing automotive safety, with practical implications for manufacturing and traffic policy
Keywords: Multiple-vehicle collisions; Sedan car; FEM simulation; Structural safety; Energy absorber